Aerobic exercise training and humoral immune response in university students - Waree Keatisuwan (Mahidol University. Mahidol University Library and Knowledge Center, 2023)
The effect of strenuous and aerobic exercise training on humoral immune response (level of IgG, IgA and IgM) and some serum proteins (serum albumin and globulin) were investigated in 10 male students from Chulalongkorn University in study I and 28 male paramedical students of Mahidol University in study II. These subjects were in similar socio-economic status and age matching. The concentration of immunoglobulins (IgG, IgA and IgM) were determined by Enzyme-Linked Immunosorbent Assay (ELISA) and serum proteins were assayed by colorimetric method. In study I, five students were randomly selected into athletic group (A) and 5 students in non-athletic group (NA). The age, weight, and height in A group were 21.5 ± 0.4 years, 61.8 ± 1.9 Kg and 168.2 ± 1.6 cm as compared to 19.1 ± 0.4 years, 54.8 ± 1.98 Kg and 166.9 ± 1.3 cm in NA group, respectively. Bicycle ergometer activity was used to maintain with 70% maximum heart rate [0.7 (MHR - RHR) + RHR] for one hour. Peak VO(,2) max in A and Na groups were 57.5 ± 3.6 ml/kg/min and 39.2 ± 1.3 ml/kg/min. respectively. The concentrations of IgG, IgA and IgM of A group before exercise were 1.52 ± 0.19, 0.147 ± 0.02 and 0.144 ± 0.004 g/dl which were similar to those of A group after exercise (1.31 ± 0.15, 0.155 ± 0.02 and 0.124 ± 0.02, respectively). However, there was no significant difference in IgG, IgA and IgM concentration of NA group 1.44 ± 0.2, 0.182 ± 0.01 and 0.116 ± 0.01 g/dl before exercise when compared with these of NA group after exercise (1.36 ± 0.18, 0.160 ± 0.01 and 0.105 ± 0.02 g/dl, respectively). In contrast, there was a significant reduction in total serum globulin of NA group from 2.42 ± 0.08 to 2.17 ± 0.1 g/dl (P < 0.01), but the serum albumin did not change. It was noted that all parameters were corrected to actual concentration of each parameter during water loss. These findings indicated that strenuous exercise at 70% VO(,2) max for one hour has no significant influence on humoral immune response especially IgG, IgA, and IgM levels. In study II, twenty-eight paramedical students were divided into 17 students of exercise training group (ET) and 11 students of control group (C). In ET group, the exercise was performed throughout 16 weeks based on aerobic exercise program, (70% MHR, 20 min/d and 3 times/wk) according to Karvonen, (1959). Heart rate in ET group was significantly decreased (P < 0.001) while peak VO(,2) max was increased (P < 0.001) after the end of aerobic exercise training. The concentration of IgG at the beginning, 8th week and 16th week were 1.22 ± 0.1, 1.28 ± 0.1 and 1.31 ± 0.1 g/dl, IgA were 0.173 ± 0.01, 0.171 ± 0.01 and 0.167 ± 0.01 g/dl, IgM were 0.120 ± 0.01, 0.115 ± 0.01 and 0.127 ± 0.01 g/dl, respectively. During exercise program the levels of IgG, IgA, IgM, albumin and globulin showed no significant difference. However, the tendency of increasing IgG level after the exercise training of 16 weeks period at the level 70% MHR (65% VO(,2) max) may be due to the recruitment of immune response in these students.